Effects of exogenous chloride ions on the migration and transformation of Cd in a soil-rice system - Fan, Haijin; Tang, Shengshuang; Long, Jian; He, Rujing; Xiao, Ziman; Hou, Hongbo; Peng, Peiqin (Frontiers in Environmental Science, 2024)
Soil cadmium (Cd) contamination has emerged as a significant global environmental concern, posing numerous risks to individual organisms and entire ecosystems. Concurrently, the global increase in pesticide usage has elevated the influx of chloride ions (Cl -) into the soil. Given Cl -'s robust ability to coordinate and complex with various heavy metal ions, understanding its influence on the migration and transformation of Cd in soil-rice systems is essential for the rational application of pesticides and the effective mitigation of soil heavy metal pollution. This study explored the impact of Cl - on the environmental behavior of Cd in the soil-rice system, focusing on growth traits, Cd uptake and accumulation by rice, and the behavior of Cd at the solid-solution phase interface. Our findings from pot and sand culture experiments reveal that during the filling period, Cd concentrations in all parts of the rice treated with CaCl2 were lower than those in the Ca(NO3)2-treated group, with Cd accumulation diminishing as Cl - concentration increased. This suggests that the filling period is critical for Cd uptake and accumulation in rice. Unlike the accompanying anion NO3 -, exogenous Cl -reduced Cd concentrations in the soil solution but increased them in rice. Notably, when the Cd/Cl ratio ranged from 0.625 to 2.5, Cl -formed predominantly CdCl + -complexes with free Cd 2+ in the soil solution, enhancing the mobilization of Cd bound to soil particles and its subsequent absorption by rice. This study aims to assess Cl -'s effect on Cd migration and transformation in soil-rice systems, providing insights for safe rice production on Cd-contaminated soils and rational use of chlorine-containing pesticides.